The Linguistic Structure and Socio-Religious Functions of the Tolak Bala Mantra in the Babadan Village - Vicky Ardi Kurniawan; Nina Queena Hadi Putri (JENTERA: Jurnal Kajian Sastra, 2026)
Oral tradition in the form of tolak bala mantras represents a form of local wisdom within Javanese society, reflecting the spiritual relationship between humans, nature, and God. This study aims to examine the linguistic structure, symbolic meaning, and socio-religious functions of tolak bala mantras in Babadan Village, Werungotok District, Nganjuk Regency, East Java. This research employs a descriptive qualitative method and was conducted on October 4, 2025. The data consist of mantra utterances and interview results involving five informants, including one village elder, two community leaders, and two local residents. Data were collected through in-depth interviews, observation, and note-taking techniques, and analyzed using the Miles and Huberman model with triangulation. The findings reveal that the tolak bala mantra reflects religious syncretism between Islamic teachings and Javanese local beliefs, functions as a form of spiritual protection, and serves as a medium for preserving cultural identity through symbolic, repetitive, and performative language structures. The implications highlight the importance of preserving mantras as oral cultural heritage that reinforces religious values, ecological awareness, and social identity. Abstrak Tradisi lisan berupa mantra tolak bala merupakan bagian dari kearifan lokal masyarakat Jawa yang merefleksikan hubungan spiritual antara manusia, alam, dan Tuhan. Penelitian ini bertujuan untuk mengkaji struktur bahasa, makna simbolik, serta fungsi sosial-religius mantra tolak bala pada masyarakat Desa Babadan, Kecamatan Werungotok, Kabupaten Nganjuk, Jawa Timur. Penelitian ini menggunakan metode deskriptif kualitatif dan dilaksanakan pada 4 Oktober 2025. Data penelitian berupa tuturan mantra dan hasil wawancara dengan lima informan yang terdiri atas satu sesepuh desa, dua tokoh masyarakat, dan dua warga. Data dikumpulkan melalui wawancara mendalam, observasi, serta teknik simak dan catat, kemudian dianalisis menggunakan model Miles dan Huberman dengan teknik triangulasi. Hasil penelitian menunjukkan bahwa mantra tolak bala merepresentasikan sinkretisme religius antara ajaran Islam dan kepercayaan lokal Jawa, berfungsi sebagai doa perlindungan spiritual, serta menjadi sarana pelestarian identitas budaya melalui struktur bahasa yang simbolik, repetitif, dan performatif. Implikasi penelitian ini menegaskan pentingnya pelestarian mantra sebagai warisan budaya lisan yang memperkuat nilai religius, kesadaran ekologis, dan identitas sosial masyarakat.